The other “Bangla-Town”: Marginality in the centre of Rome - Piazzoni, Francesca (Migration Letters, 2021)
Poor immigrants in cities across the world challenge exclusion by appropriating and transforming urban spaces. Scholars have tended to explore these migrant urbanisms by focusing on low-income, “marginal” districts that remain separate from prime spaces like historic downtowns. This paper widens such a focus by analysing how Bangladeshi immigrants inhabit the touristic centre of Rome, an iconic space designed to normalise—and capitalise upon—dominant constructions of who belongs to the Italian city. Roughly 2,000 immigrants eke out a living in Rome’s centre by selling trinkets to tourists. Drawing from observations and interviews, I detail how diverse vendors emplace their own Rome by working, hiding, praying, and relaxing in its iconic landscapes. Contingent, and yet persistent, the urbanisms enacted by the vendors destabilise normative logics of identity and call attention to prime spaces as potential arenas of insurgency.